Short-term air pollution, cognitive performance and nonsteroidal anti-inflammatory drug use in the Veterans Affairs Normative Aging Study - Gao, Xu; Coull, Brent; Lin, Xihong; Vokonas, Pantel; Spiro, Avron; Hou, Lifang; Schwartz, Joel; Baccarelli, Andrea A. (Nature Aging, 2021)
Air pollution, especially fine particulate matter (PM2.5), may impair cognitive performance1–3, but its short-term impact is poorly understood. We investigated the short-term association of PM2.5 with the cognitive performances of 954 white males measured as global cognitive function and Mini-Mental State Examination (MMSE) scores and further explored whether taking nonsteroidal anti-inflammatory drugs (NSAIDs) could modify their relationships. Higher short-term exposure to PM2.5 demonstrated nonlinear negative associations with cognitive function. Compared with the lowest quartile of the 28-d average PM2.5 concentration, the 2nd, 3rd and 4th quartiles were associated with 0.378, 0.376 and 0.499 unit decreases in global cognitive function score, 0.484, 0.315 and 0.414 unit decreases in MMSE score and 69, 45 and 63% greater odds of low MMSE scores (≤25), respectively. Such adverse effects were attenuated in users of NSAIDs compared to nonusers. This study elucidates the short-term impacts of air pollution on cognition and warrants further investigations on the modifying effects of NSAIDs.